1996
DOI: 10.1073/pnas.93.26.15289
|View full text |Cite
|
Sign up to set email alerts
|

Induction of HSP70 and polyubiquitin expression associated with plant virus replication

Abstract: By examining the front of virus invasion in immature pea embryos infected with pea seed-borne mosaic virus (PSbMV), the selective control of different host genes has been observed. From our observations, the early responses to PSbMV replication can be grouped into three classes, inhibited host gene expression, induced host gene expression, and no effect on a normal host function. The expression of two heat-inducible genes encoding HSP70 and polyubiquitin was induced coordinately with the onset of virus replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
107
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 30 publications
11
107
0
Order By: Relevance
“…We and others have reported the induction of HSP70 by a wide range of viruses in diverse host plants, including pea (Pisum sativum), N. benthamiana, squash (Cucurbita pepo), tobacco (Nicotiana tabacum), and Arabidopsis (Aranda et al, 1996;Escaler et al, 2000;Havelda and Maule, 2000;Jockusch et al, 2001;Whitham et al, 2003). Based on the differential induction of heat-inducible genes Figure 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have reported the induction of HSP70 by a wide range of viruses in diverse host plants, including pea (Pisum sativum), N. benthamiana, squash (Cucurbita pepo), tobacco (Nicotiana tabacum), and Arabidopsis (Aranda et al, 1996;Escaler et al, 2000;Havelda and Maule, 2000;Jockusch et al, 2001;Whitham et al, 2003). Based on the differential induction of heat-inducible genes Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…those showing high levels of virus replication and viral genome expression) accumulate HSP70 mRNA and protein (Aranda et al, 1996;Escaler et al, 2000). This phenomenon applies to infections with a diverse range of viruses, including members from the Potyvirus, Tobravirus, Potexvirus, Geminivirus (Aranda et al, 1996;Escaler et al, 2000), and Cucumovirus (Havelda and Maule, 2000) genera. While the detailed mechanism of HSP70 induction by plant viruses has not been investigated, for animal viruses specific viral proteins have been shown to be active (Aranda and Maule, 1998, and refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, it was reported that HSP70 and HSP90 are essential components in the INF1-mediated hypersensitive response in Nicotiana benthamiana, and that they function upstream or independent of the MAPK cascade [23]. Moreover, various reports describe that HSP70 expression in plants is induced upon infection with pathogens [23][24][25][26], but more detailed analysis of HSP70 expression profiles during plant-pathogen interactions are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were first subjected to RT-PCR to confirm the virus infection and then subjected to qRT-PCR to quantify the expression level of HSFs. The CPR response associated with virus infection is highly localized, being focused on cells actively involved in virus multiplication and virus and virus genome expression (Aranda et al, 1996). As such, the level of induction of HSFs was less than observed in response to AZC or heat shock.…”
Section: Hsfa2-ii Rna Is Not Active and Is Degraded By Non-sense-medimentioning
confidence: 99%